The Treatment Strategy of Cleidocranial Dysplasia: Combined Orthodontic and Orthognathic Treatment. Issue 6 (September 2019) - Li, Juan; Shen, Jiawei; Xu, Ji; Weng, Luxi; Pan, Jiale; Lin, Jun
Abstract : Abstract: Cleidocranial dysplasia is a rare autosomal-dominant condition that affects ossification. The main symptoms of this cleidocranial dysplasia patient include craniofacial abnormalities, hypoplasia of clavicles, narrow thorax, retarded exfoliation of deciduous teeth, retarded eruption of permanent teeth, and multiple impacted supernumerary teeth. The aim of this treatment was to correct the craniofacial abnormalities and provide an adequate functional reconstruction of the occlusion. The patient was treated with a multidisciplinary therapeutic protocol including removal of supernumerary teeth, surgical exposure of impacted teeth, orthodontic, and orthognathic surgery. After 6 years' follow-up, the treatment objectives of acceptable occlusion, normal function, and acceptable profile were achieved. Abstract : Supplemental Digital Content is available in the text